2003
DOI: 10.1016/s0008-6363(03)00368-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endotoxic shock on right ventricular systolic function and mechanical efficiency

Abstract: In the very early phase of endotoxinic shock, right ventricular-vascular coupling is preserved by an increase in RV contractility. Later, myocardial oxygen consumption and energetic cost of RV contractility are increased, as evidenced by the decrease in RV efficiency, and right ventricular-vascular uncoupling occurs. Therefore, therapies aiming at restoring right ventricular-vascular coupling in endotoxic shock should attempt to increase RV contractility and to decrease RV afterload but also to preserve RV mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 30 publications
8
44
0
3
Order By: Relevance
“…For the pulmonary circulation, our results evidenced significant correlation between both methods, as well as between E a ‫ء‬ (PV) and RT/T, despite dramatic changes in pulmonary vascular compliance. Our laboratory previously showed a concordant evolution between E max /E a and stroke work in pulmonary embolism or septic shock (6,13,15). This could be explained by higher basal pulmonary vascular compliance compared with the values obtained on the systemic circuit.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For the pulmonary circulation, our results evidenced significant correlation between both methods, as well as between E a ‫ء‬ (PV) and RT/T, despite dramatic changes in pulmonary vascular compliance. Our laboratory previously showed a concordant evolution between E max /E a and stroke work in pulmonary embolism or septic shock (6,13,15). This could be explained by higher basal pulmonary vascular compliance compared with the values obtained on the systemic circuit.…”
Section: Discussionmentioning
confidence: 67%
“…Our laboratory previously showed that, in heart failure due to pulmonary embolism and sepsis, the decreased value of E max /E a was related to an impaired use of energy by the failing heart (6,13,15). In combination with E max , E a (PV) appears to be a simple way to characterize ventriculo-arterial interaction (18,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…These 9 subjects were divided into two groups with 5 pigs induced with pulmonary embolism (Desaive et al (2005); Ghuysen et al (2008)). The remaining 4 are induced with septic shock, and treated with haemofiltration starting at two hours (Lambermont et al (2003)). Both studies were under the control of the ethics committee of the medical faculty of Liege, Belgium.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it provides a good set of data to watch to progression of the disease state. For details see (Desaive et al (2005); Ghuysen et al (2008);Lambermont et al (2003)). …”
Section: Methodsmentioning
confidence: 99%
“…19 Endotoxic shock-induced increase in PVR was associated with early preservation of RV-arterial coupling but deterioration as soon as 1 hour after the initial insult because of an unsustained adaptive increase in contractility. 21 Chronic aortopulmonary shunting as a model of persistent ductus arteriosus in growing piglets was associated with preserved RV-arterial coupling after 3 months, 24,37 but with uncoupling after 6 Note: E max : maximum right ventricular elastance; E a : pulmonary arterial elastance; PA: pulmonary artery; AP; aortopulmonary; RVF: right ventricular failure. months because of RV systolic function failure.…”
Section: Coupling Of Systolic Function To Afterloadmentioning
confidence: 99%